An Analysis of Makovsky's Border Proposal in Light of Palestinian Needs. (September 2014) - Wilson, Andrew M.
Abstract The border proposal of David Makovsky, who, served as an advisor to Martin Indyk during the recent Israeli‐Palestinian peace talks, is analyzed from the standpoint of viable contiguity — the degree to which the border, particularly where there is Israeli annexation of settlement blocs, offers provision for access, living space, and transportation infrastructure for the Palestinian population in adjacent areas. While at some locales his proposed border improves contiguity for Palestinians compared with the current situation unilaterally imposed by Israel, more attention needs to be given to the ways it would adversely affect the quality of life of the Palestinian population in the cities and villages adjacent to those settlement blocs. This leads to the suggestion that a more comprehensive solution to border issues will feature the establishment of joint economic zones and binational administrative authorities, which can manage the entanglement of roads and populations in ways that will maximize the potential for economic development.